1975
DOI: 10.1246/bcsj.48.2597
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Polyacrylamide Molecules in Aqueous Solutions by High-speed Stirring

Abstract: SynopsisIt has been observed that the viscosity of polyacrylamide (PAM) solution decreased with an increase in high-speed stirring time. The viscosities of PAM solutions decrease initially and then remain constant as the stirring time is increased. The final values depend on the stirring speed. This decrease was assumed to be due to a change in the dissolved state and/or the degradation of PAM molecules. It was discovered through experimentation that the molecular weight decreased, implying that the PAM molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…When exposed to a shear environment, high molecular weight formulations typically see an initial steep decline in viscosity which plateaus as the smaller remaining molecules flow around the source of shear more easily. Nagashiro et al (1975) saw viscosity drop quickly as molecular weight fell from 5 to 3 Mg mor 1 . PAM solutions or PAM applied to targets can also experience gradual (e. g., weeks) reduction of molecular weight due to environmental exposure, particularly UV light, or through gradual unfolding of the macromolecule (Molyneux, 1983).…”
Section: Pam Properties Affecting Efficacymentioning
confidence: 99%
“…When exposed to a shear environment, high molecular weight formulations typically see an initial steep decline in viscosity which plateaus as the smaller remaining molecules flow around the source of shear more easily. Nagashiro et al (1975) saw viscosity drop quickly as molecular weight fell from 5 to 3 Mg mor 1 . PAM solutions or PAM applied to targets can also experience gradual (e. g., weeks) reduction of molecular weight due to environmental exposure, particularly UV light, or through gradual unfolding of the macromolecule (Molyneux, 1983).…”
Section: Pam Properties Affecting Efficacymentioning
confidence: 99%
“…It was reported that a shearing hydrodynamic field induced chain bond scissions leading to a decrease in the molecular weight of the polyacrylamide and then to a decrease in intrinsic viscosity of PAM solutions (Paterson and Abernathy 1970;Abdel-Alim and Hamielec 1973;Nagashiro et al 1975;Povkh and Chernyuk 1986;Nguyen and Boger 1998;Avadiar et al 2013). In particular, mechanical degradation of polymers used for drag reduction in a turbulently flowing liquid has been studied by several authors (Rho et al 1996;Vlachogiannis et al 2003;Pereira and Soares 2012).…”
Section: Mechanical Degradationmentioning
confidence: 99%
“…In the PAM-treated soil, the effect of PAM solution-based adhesion and adsorption on soil is that small soil particles become aggregated, which enhances the overall stability of soil aggregates and limits crust formation at the soil surface, resulting in an increase in the infiltration rate and decrease in runoff. However, excess dissolved PAM could clog soil pores 35 37 , thus forming a sealed layer on the surface soil similar to surface crust resulting from the impact of raindrops. Therefore, runoff rates were reduced with 1 and 2 g·m −2 PAM application rates but increased with4 g·m −2 PAM application rates.…”
Section: Resultsmentioning
confidence: 99%
“…The overland-flow depth on the sloped land is very thin, approximately0.1–0.5 mm 35 . Therefore, the ponding water was neglected, and the runoff can be expressed as follows: Substituting Eq.…”
Section: Methodsmentioning
confidence: 99%